Pemberdayaan Masyarakat dengan Pembentukan Kelembagaan Model Youth Forest Care untuk Pelestarian Hutan Adat Wonosadi Berbasis Cultivating Local Wisdom - Aji, Bayu; Arwansyah, Noval; Ataya, Diva Tia; Darmawan, Yudi; Febrianti, Shita Az Zahra; Sakti, Rakha Sahasika; Qomari, Asri Arti Nur (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Wonosadi Customary Forest in Beji Village, Kapanewon Ngawen, Gunungkidul, is a forest area that has high local wisdom value, but is currently facing serious challenges in its conservation efforts due to environmental degradation and the lack of structured and organized community participation governance, especially the younger generation. This research aims to empower the community through the establishment of a “Youth Forest Care” institution based on cultivating local wisdom with the hope of increasing active participation in efforts to preserve the Wonosadi Customary Forest. This service activity involved 20-25 people from among the youth and young people of Beji Village who were selected based on certain criteria. The implementation method includes a participatory approach with stages that include problem identification, Focus Group Discussion, preparation of local wisdom-based training materials, training implementation, institutional formation, and evaluation and monitoring. The results of the activities showed an increase in ecological awareness and active participation of the community in conservation activities as well as the formation of institutions recognized by the community and village government. This institution is expected to become a model of local wisdom-based community empowerment that can be replicated in other areas with similar characteristics.